Incidence and costs of cardiovascular events in Spanish patients with type 2 diabetes mellitus: a comparison with general population, 2015. Issue 1 (2nd August 2020) - Jodar, Esteban; Artola, Sara; Garcia-Moll, Xavier; Uría, Estefany; López-Martínez, Noemí; Palomino, Rosa; Martín, Virginia
Abstract : Introduction: Cardiovascular (CV) disease affects a high percentage of patients with type 2 diabetes mellitus (T2DM), especially in the hospital setting, impacting on mortality, complications, quality of life and use of health resources. The aim of this study was to estimate the incidence, mean length of hospital stay (LOHS) and costs attributable to hospital admissions due to CV events in patients with T2DM versus patients without diabetes mellitus (non-DM) in Spain. Research design and methods: Retrospective observational study based on the Spanish National Hospital Discharge Database for 2015. Hospital admissions for patients aged ≥35 years with a diagnosis of CV death, non-fatal acute myocardial infarction (AMI), non-fatal stroke, unstable angina, heart failure and revascularization were evaluated. The International Classification of Diseases, Ninth Revision (250.x0 or 250.x2) coding was used to classify records of patients with T2DM. For each CV complication, the hospital discharges of the two groups, T2DM and non-DM, were precisely matched and the number of hospital discharges, patients, LOHS and mean cost were quantified. Additional analyses assessed the robustness of the results. Results: Of the 276 925 hospital discharges analyzed, 34.71% corresponded to patients with T2DM. A higher incidence was observed in all the CV complications studied in the T2DM population, with a relative risk exceeding 2 in all cases. The mean LOHS (days) was longer in the T2DM versus the non-DM group for: non-fatal AMI (7.63 vs 7.02, p<0.001), unstable angina (5.11 vs 4.78, p=0.009) and revascularization (7.96 vs 7.57, p<0.001). The mean cost per hospital discharge was higher in the T2DM versus the non-DM group for non-fatal AMI (€6891 vs €6876, p=0.029) and unstable angina (€3386 vs €3304, p<0.001). Conclusions: Patients with T2DM had a higher incidence and number of hospital admissions per patient due to CV events versus the non-DM population. This generates a significant clinical and economic burden given the longer admission stay and higher costs associated with some of these complications.